Re-migration behaviour and expected duration of stay of guest-workers in Germany - Viktor Steiner; Johannes Velling (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1992)
We analyze guest-workers' expected duration of stay in Germany within an econometric model taking into account the important distinction between permanent and temporary stayers, where the expected duration of stay for the latter is differentiated in short-term, medium-term and long-term stayers. The model is estimated for household heads on the first six waves of the German Socio-Economic Panel taking advantage of the panel structure of our data base to obtain efficient parameter estimates.
Keywords: 330